(untitled) (Eurasian Journal of Philology Science and Education, 2025)
The purpose of the study is the formation of students’ language and speech competencies in Kazakh language lessons using audiovisual materials with the development of listening skills. In the course of solving this practical goal, the means of audiovisual education were identified, including the practical significance of films as didactic material; a set of educational tasks was developed for the development of students’ language and speech competencies in Kazakh language lessons. Mastering students’ listening skills is an important stage in learning the Kazakh language. Types of speech activity, in particular, the level of mastery of listening and writing skills, can serve as an objective indicator of a student’s language maturity. The proposed methodological approaches at the motivationally oriented, analytical-synthetic and reflexive-control stages of working with audiovisual materials create conditions for conscious perception and accurate understanding of the information heard/seen in the Kazakh language lesson, the development of oral and written speech of students. A wide variety of tasks performed at the analytical and synthetic stage of analyzing the structural and meaningful information of the film and the reflexive control stage contributes to the realization of the creative potential of students as a communicative personality. The tasks proposed when working with audiovisual material are aimed at developing the student’s abilities for familiarization, review, critical thinking, information retrieval information. Keywords: listening, skills, means of audiovisual learning, language competence, speech competence, communicative approach.